PENDEKATAN INDEKS DAYA SAING DAN PENGARUH SEKTOR PARIWISATA DALAM MENINGKATKAN EKONOMI DAERAH KOTA BATU - Niken Puspitasari; Farida Rahmawati (Bina Ekonomi, 2022)
Batu City has an artificial tourism base, which could be a strategic tourism destination in East Java province. The tourism competitiveness index analysis and the effect of the tourism sector on local generated revenue were also used to analyze the economic growth that has come to Batu City's tourism sector. In studying the effect of the tourism sector on locally generated revenue in Batu City, the research uses the quantitative method with the calculation of the tourism competitiveness index and multiple rectilinear regression. The results obtained by Batu City indicate that tourism competitiveness is already good in the refinement development stage, as indicated by the pillars Safety and Security, Human Resources and Labor Market, Environmental Sustainability, natural resources, Business Environment, Price Competitiveness, and Ground and Port Infrastructure. But in the Health and Hygiene, ICT Readiness, Prioritization of Travel & Tourism, International Openness, and Tourist Service Infrastructure are still in the early stages of development. And the tourism sector, which is related to the tourism competitiveness index, has to have a significant and positive effect on local generated revenue, whereas the room occupancy rate and total population have no significant and negative effect.